Neonatologist-performed point-of-care abdominal ultrasound: What have we learned so far? - Priyadarshi, Archana; Rogerson, Sheryl; Cruzado, Rommel; Crow, Amanda; Hinder, Murray; Popat, Himanshu; Soundappan, Soundappan S. V.; Badawi, Nadia; Tracy, Mark (Frontiers in Pediatrics, 2023)
This review describes the sonographic appearances of the neonatal bowel in Necrotising enterocolitis. It compares these findings to those seen in midgut-Volvulus, obstructive intestinal conditions such as milk-curd obstruction, and slow gut motility in preterm infants on continuous positive airway pressure (CPAP)-CPAP belly syndrome. Point-of-care bowel ultrasound is also helpful in ruling out severe and active intestinal conditions, reassuring clinicians when the diagnosis is unclear in a non-specific clinical presentation where NEC cannot be excluded. As NEC is a severe disease, it is often over-diagnosed, mainly due to a lack of reliable biomarkers and clinical presentation similar to sepsis in neonates. Thus, the assessment of the bowel in real-time would allow clinicians to determine the timing of re-initiation of feeds and would also be reassuring based on specific typical bowel characteristics visualised on the ultrasound.